580409783_5_Ch0-��解�

580409783_5_Ch0-��解� - Ch0-h 1h...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Ch0-h 1h ðV²º h Rn W 1≤i ≤ n n ρ∞ (x, y ) = max | xi − y i | ρ p (x, y ) = (∑ | xi − y i | p )1/ p i =1 (1 ≤ p < ∞) º · ¨♠ @ 7C , F“{@ 2( ¨·♠ º* ρ∞ ρp Ú c| Wi ρ ( x, y ) W ˜♠ ·º * ρ ( x, y ) % ρ ( x, y ) @ 1 + ρ ( x, y ) º ¨·♠ * ) 1( % ρ ( x, y ) ( Q ρ ( x, y ) ≥ 0 % ∴ ρ ( x, y ) ≥ 0 % x = y ⇔ ρ ( x , y ) = 0 ⇔ ρ ( x, y ) = 0 ( ρ ( y, x) ρ ( x, y ) % % ρ ( y, x ) = = = ρ ( x, y ) 1 + ρ ( y , x ) 1 + ρ ( x, y ) ˜·ºª * ˜·ºª f (t ) = * ·ºª i t 1+ t * R ¨·ºª º²VÈ ) 2( ) 3( 1 *♦ ·ºª (1 + t ) 2 ρ ( x , z ) ≤ ρ ( x, y ) + ρ ( y , z ) f '(t ) = % ρ ( x, z ) = t ∈ R h f '(t ) > 0 f * (ªt )º · ˜ f ( ρ ( x, z )) ≤ f ( ρ ( x, y ) + ρ ( y, z )) ρ ( x, z ) ρ ( x, y ) + ρ ( y , z ) ≤ 1 + ρ ( x , z ) 1 + ρ ( x, y ) + ρ ( y , z ) ρ ( x, y ) ρ ( y, z ) = + 1 + ρ ( x , y ) + ρ ( y , z ) 1 + ρ ( x, y ) + ρ ( y , z ) ρ ( x, y ) ρ ( y, z ) ≤ + 1 + ρ ( x, y ) 1 + ρ ( y , z ) % % = ρ ( x, y ) + ρ ( y , z ) % ρ ( x, y ) € 1( 2( 3( ( z“F@{ ρ ( x, y ) ρ ( y, z ) ρ ( x, z ) + − ≥ 0 F ,“7C{ @ @ 1 + ρ ( x, y ) 1 + ρ ( y , z ) 1 + ρ ( x, z ) t f (t ) = € 1+ t ( 3( ρ ( α X, 0 0= α ρ ( X, 000 ) ) ) ) Q ρ ( α X, 0 0= α ρ ( X, 000 Wº ² U ˆ Q (W,ρ) ( W , g)* ≡ ª″ È⌡ (W,ρ) ( W , g)≡8″ *ª ρ²U ˆ ) )ª 1( ρ ( α X, 0 0= α ρ ( X, 00 * ≡ 2( ρ (x, y ) = ρ (x + a, y + a) ∀a ∈ ªW² ÷ *º x = ρ (x, 0) h W * i ª º g Èõ ² 3 á| ,e ç + x + y = ρ (x + y , 0) = ρ (x, −y ) ≤ ρ (x, 0) + ρ (− y, 0) = ρ (x, 0) + −1 ρ (y , 0) =x+y 4( C [ a, b ] € “ y x* Ð ( ª t º )U ¸²F ρ ( x, y ) = max x ( t ) - y ( t ) ª º ² Èõ i * 1º( ² Èõ ª i C [ ay ,* bº ] ² “F T Ъ a£ t £ b " x, y Î C [ a, b ] ρ ( x, y ) ²º Sø ρ ( x, y ) ≥ 0 ρ ( x, y ) = max x(t ) − y (t ) = 0 x= y a ≤t ≤b ∀t ∈ [a, b], x(t ) = y (t ) x= y 2( ( x(t ) ≡ y (t ), t ∈ [a, b] ρ ( x, y ) = 0 ρ ( x, y ) = max x(t ) − y (t ) = max y (t ) − x(t ) = ρ ( y, x) ♠ ≡ *″ È⌡ ρ ( x, y ) = max x (t ) − y (t ) a ≤t ≤b a ≤t ≤b a ≤t ≤b a ≤t ≤b 3( = max [ x (t ) − z (t )] + [ z (t ) − y (t )] ≤ max( x(t ) − z (t ) + z (t ) − y (t ) ) a ≤t ≤b ≤ max x(t ) − z (t ) + max z (t ) − y (t ) a ≤t ≤b a ≤t ≤b = ρ ( x, z ) + ρ ( z , y ) 5( C [ a, b ] € x ( tF “ )* y ≡T ªÐ ″ p æb ö ρ ( x, y ) = çò x ( t ) - y ( t ) dt ÷ Qp ≥ 1 ÷ ça è ø 1/ p ∞ > p ≥1 1( ∗ ♠ ≡ ¸× ≠ ρ ( x, y ) ≥ 0 1/ p p æb ö ρ ( x, y ) = çò x ( t ) - y ( t ) dt ÷ = 0 Q x(t ) i y (t* )ªÅ hºÐy“F ÷ ça è ø x(t ) - y (ª tº )² Øø x(t ) ≡ y (t ), t ∈ [a, b] ø * ) ª º ² Øø * x(t ) ≡ y (t ), t ∈ [a, b] x(t ) - y (t ) º 0, t Î [a, b] Q ρ ( x, y ) = 0 ) ( 0( ) 2( ( p p æb ö æb ö ρ ( x, y ) = çò x ( t ) - y ( t ) dt ÷ = çò y ( t ) - x ( t ) dt ÷ = ρ ( y, x ) ÷ ça ÷ ça è ø è ø 1/ p 1/ p Q3( ¹ * ¸´≡ ª p æb ö ρ ( x, y ) = çò x ( t ) - y ( t ) dt ÷ ÷ ça è ø 1/ p p æb ö = çò [ x ( t ) - z ( t ) ] + [ z (t ) - y (t )] dt ÷ ÷ ça è ø 1/ p 1/ p p p æb ö æb ö £ çò x ( t ) - z ( t ) dt ÷ + çò z ( t ) - y ( t ) dt ÷ ( ÷ ça ÷ ça è ø è ø 1/ p Minkovski = ρ ( x, z ) + ρ ( z , y ) Q p =¹ ¥´ ¸ª º * ª º ² Øø 6( + | | 3 , ρ ( x, y ) = max x ( t ) - y ( t ) a£ t £ b " x, y Î C [ a, b ] Q 5 ø eá parallelogram identity : 2 2 * ª W Øø º² x = x, x 2 1/ 2 àø ªº ¹ ÷ ´ x+ y + x− y =2 x + y ♠ ≡ ″ ¬ ∗ polarization identity : 1 2 x, y = x+ y − x− y 4 ( 2 ) ∀x, y ∈ W ( 2 ) W ¸× ª ≡ ≠ 1 *¸ ª ≡ ≠ × x + y = x + y, x + y = x, x + x, y + y , x + y , y x - y = x - y, x - y = x, x - x , y ①+② Q x + y + x - y = 2( x, x + y, y ) = 2 x + y 2 2 2 2 …① y , x + y, y …② ( 2 2 ) ) 2( (1 ) ①-② Q x + y - x - y = 2( x, y + y, x ) x, y = y , x = y , x ) 2 * 2 2 W iº ¹ ¸´* ª 2 x + y - x - y = 4 x, y ) x, y = 1 2 x+ y − x− y 4 ( 2 ) 7( ( W x, y = 0 x y νºª*Ðy“F a) x ⊥ y⇒ x+ y = x− y Q x ^ y \ x, y = 0 Q 6 2 ①Q②Q 2 2 x + y = x + y …③ x- y = x + y ) b) 2 2 2 x+ y = x- y 2 2 2 x ⊥ y ⇒ x + y = x + y ÷˜ ♠ ≡α * a ③Q x ⊥ y , ∀y ∈ W ⇔ x = 0 c) " Þ " QQ " y Î W QQ x ^ y Q y=x) x^xQ x, x = x = 0 ) 2 x =0) ) x=0) y " Ü " QQ x = 0 \ " y Î W QQ x, y = 0, y = 0g , y = 0g y, y = 0 Q x^yQ d) X ,Y ⊂ W X ⊥Y ⇒ X ⊂Y⊥ Y ⊂ X⊥ Y ^ = {x | x Î W , x ^ Y } Q X ^ = { y | y Î W , y ^ X } Q X ^Y \ i i i i i ix Î iX i, i i y Î Y , i Q Y Ì X^ x^y X Ì Y^ ...
View Full Document

This note was uploaded on 03/28/2011 for the course ELECTRICAL 30230104 taught by Professor Yongren during the Fall '11 term at Tsinghua University.

Ask a homework question - tutors are online